1991
DOI: 10.1089/aid.1991.7.971
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of HIV Infection by Passive Immunization with HIV Immunoglobulin

Abstract: The use of a human immunodeficiency virus (HIV) immune globulin (HIVIG) in prevention of HIV infection in chimpanzees was investigated in the hope of ultimate application to interruption of vertical transmission. In previous experiments, no protection was observed when relatively high challenge doses were used. This study shows that HIVIG protected against a challenge dose (10 CID50) tenfold lower than that used previously. The protected animal remained free of HIV infection as determined by cocultivation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(86 citation statements)
references
References 8 publications
2
84
0
Order By: Relevance
“…3). This is consistent with studies of patients, where HIVIG did not clear HIV either (Prince et al, 1991). However, some beneficial effect cannot be excluded, as in our murine model and in patients these antibodies appear to reduce the number of infected cells significantly (Figs 1 and 3; Prince et al, 1991).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3). This is consistent with studies of patients, where HIVIG did not clear HIV either (Prince et al, 1991). However, some beneficial effect cannot be excluded, as in our murine model and in patients these antibodies appear to reduce the number of infected cells significantly (Figs 1 and 3; Prince et al, 1991).…”
Section: Discussionsupporting
confidence: 92%
“…The antiserum used was the anti-HIV-1 immunoglobulin (HIVIG) (Schuitemaker et al, 1993a, b). This contains polyclonal specific anti-HIV-1 antibodies (Schuitemaker et al, 1993a, b;Prince et al, 1988Prince et al, , 1991. Active immunization studies are described for the MV vaccines because HIV-I vaccines have not been shown to give effective protection.…”
Section: Methodsmentioning
confidence: 99%
“…Animal studies have demonstrated that neutralizing antibodies elicited by a simian immunodeficiency virus (SIV) vaccine can at least slow disease progression (56), while direct administration of antibodies matched to the chal-lenge virus can block transmission (16,44). Studies of natural MCTC have yielded conflicting results (2,3,7,20,26,31,32,48), although possibly for identifiable reasons.…”
Section: Subtype C Human Immunodeficiency Virus Type 1 (Hiv-1c) Contimentioning
confidence: 99%
“…Vaccine protection also has been reported in a number of trials using the simian immunodeficiency virus (SIV)' /macaque model (for review see reference 6). Serum antibody responses might be an important element of vaccine protection because hyper-immune globulin prepared from asymptomatic, seropositive humans or macaques, protected chimpanzees from HIV-1 infection (7,8), and macaques from HIV-2 and SIV infection (9), respectively. Protection from HIV-l infection has also been observed in chimpanzees that had been passively immunized with a neutralizing human monoclonal antibody ( 10).…”
Section: Introductionmentioning
confidence: 99%